PENGARUH METODE QIRO’ATI DALAM PEMBELAJARAN BACA TULIS AL-QUR’AN TERHADAP HASIL BELAJAR (STUDI KASUS DI MI TARBIYATUL ATHFAL) - Fahrizal, Ahmad Zul; Suprapto (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research is motivated by the low ability of students in reading the Qur’an, especially because it does not yet comply with the rules of Tajwid. This can be seen from the previous year's learning outcomes, where the classical learning completeness had not been achieved. This study aims to improve students' learning outcomes and to correct the reading and writing of Qur’anic letters. This research uses a quantitative descriptive method with correlational analytic techniques. The total population involved was 291 students, while the sample used consisted of 22 students in class 5.A. The data collection techniques used by the researcher included observation, oral tests in the form of pre-tests and post-tests, and documentation. In this study, a comparison of data was conducted, namely by comparing the calculated t-value (T-Count) with the t-table value to obtain conclusions and research results. The t-table value in this study was determined using a two-tailed t-table with the formula N-1. It is known that the research sample consisted of 22, so 22-1 equals 21, and based on the t-table, the value in row 21 is 2.080. Meanwhile, the results of the paired sample test above show that the calculated t-value is 5.273. This means that the calculated t-value is greater than the t-table value, so it can be concluded that there is an effect of the Qiro’ati method on the effectiveness of learning to read and write the Qur’an in the Qur’an and Hadith subject for grade V at MI Tarbiyatul Athfal.